Prognostic Significance of Organ Dysfunction in Cats With Polytrauma - Murgia, Elsa; Troia, Roberta; Bulgarelli, Cecilia; Pelizzola, Marco; Foglia, Armando; Dondi, Francesco; Giunti, Massimo (Frontiers in Veterinary Science, 2019)
Polytrauma is a common emergency condition in small animals and is frequently associated with higher morbidity and mortality rates compared to minor trauma. Multiple Organ Dysfunction Syndrome (MODS) is a major complication of extensive traumatic injury, carrying a high risk of death despite intensive care treatment. Little is known about the prevalence and the prognostic impact of MODS in feline polytrauma. The current study aimed to prospectively evaluate the occurrence and the prognostic significance of organ dysfunction at admission in a population of polytraumatized cats. Cats with polytrauma requiring intensive care unit hospitalization were included and categorized according to outcome (survivors/non-survivors). Clinical and clinicopathological data, including scores of disease severity [Animal Trauma Triage Score (ATTS), APPLEfast, and APPLEfull], selected organ dysfunction and presence of MODS were evaluated upon admission, and analyzed with respect to mortality. Non-parametric statistics was performed and P < 0.05 was considered significant. Thirty-eight cats met the inclusion criteria: 8/38 (21%) had penetrating trauma, while 30/38 (79%) had blunt trauma. The overall in-hospital mortality was 37% (14/38). Cats with evidence of MODS upon admission had significantly higher frequency of death compared to cats without MODS (9/14 vs. 2/24 P = 0.0004). Hemostatic dysfunction, respiratory dysfunction, and MODS upon admission were significantly associated with mortality in the univariate logistic regression analysis (P = 0.005, P = 0.001, P = 0.001, respectively). The values of APPLEfast, APPLEfull, and ATTS were independently associated with a higher risk of death and positively correlated with the number of dysfunctional organs (P = 0.025, P = 0.004, P = 0.003, r = 0.57, P = 0.0002; r = 0.59, P = 0.0001; r = 0.55, P = 0.0003, respectively). Multiple Organ Dysfunction Syndrome is a common complication of feline polytrauma and its development is associated with increased disease severity and worse outcomes. The presence of hemostatic dysfunction and respiratory dysfunction upon admission is associated with a higher risk of death. The ATTS and the APPLE scores are useful prognostic tools for the assessment of cats with polytrauma.